Research in the history of economic thought and methodology. vol. 40, including a symposium on the work of François Perroux - Fiorito, Luca, 1967-; Scheall, Scott; Suprinyak, Carlos Eduardo (Research in the history of economic thought and methodology ;, 2022)
Volume 40C of Research in the History of Economic Thought and Methodology features a symposium on the work of the controversial French economist François Perroux, edited by Katia Caldari and Alexandre Mendes Cunha, and a collection of book reviews of David M. Levy and Sandra J. Peart's (2020) Towards an Economics of Natural Equals: A Documentary History of the Early Virginia School.